HipSim — hip fracture surgery simulation utilizing the Learning Curve–Cumulative Summation test (LC-CUSUM) - Rölfing, Jan Duedal; Jensen, Rune Dall; Paltved, Charlotte (Acta Orthopaedica, 2020)
Background and purpose — Virtual reality simulation of hip fracture surgery is available for orthopedic residents nationwide in Denmark. Summative assessment of learning applying the learning curve cumulative summation test (LC-CUSUM) has not been utilized in orthopedic simulation training. The strength of the LC-CUSUM is that it assumes incompetency and signals competency based on solid statistics. We investigated the LC-CUSUM characteristics of novices stepwise mastering the simulated dynamic hip screw (DHS) procedure. Material and methods — 32 1st-year orthopedic residents participated in HipSim and its 3 subsequent LC- CUSUM evaluations: placing a Kirschner wire, placing a Kirschner wire in different patients, and performing the entire DHS procedure in different patients. The career status of the participants, i.e., still working in orthopedics or in another specialty was recorded ≥ 2 years after participation and associated with the simulation performance (passed/ failed). Results — 13/14 participants passing HipSim according to LC-CUSUM were still working in orthopedics, while 9/18 participants failing HipSim had quit orthopedics at ≥ 2 years follow-up. The simulator-generated feedback did not statistically significantly differ between the groups. Interpretation — LC-CUSUM and its summative pass/ fail assessment of each simulation was feasible in this formative simulation program. Clinical educators can be reassured that participants passing HipSim are likely to continue to 2nd–5th year of residency, while failing HipSim should raise concerns and trigger career counselling and clinical supervision. The motivational aspect of LC-CUSUM pass/ fail assessment when designing formative simulation training warrants further research.